2008
DOI: 10.1016/j.ijgo.2008.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Identifying biomarkers of endometriosis using serum protein fingerprinting and artificial neural networks

Abstract: This method shows great potential in identifying biomarkers to be used for endometriosis screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 24 publications
0
26
1
Order By: Relevance
“…In our study, the total number of patients included was much higher (nϭ254) than in previous reports (median 87, range 32-141; Table 4). Our study population was also well characterized with respect to menstrual cycle phase, whereas previous studies did not include any cycle phase description 8,9,11,12,14 or did not confirm cycle phase descrip-…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the total number of patients included was much higher (nϭ254) than in previous reports (median 87, range 32-141; Table 4). Our study population was also well characterized with respect to menstrual cycle phase, whereas previous studies did not include any cycle phase description 8,9,11,12,14 or did not confirm cycle phase descrip-…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of the markers identified with this method are either of low sensitivity and specificity, their positive predictive value is not accurate enough to be used for routine clinical purposes, or even their molecular nature is not determined. These studies have focused primarily on blood and tissues (i.e., endometrial, endometriotic, peritoneal) to analyze proteomes in endometriosis (30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…13,14 In a previous study, we identified five potential biomarkers in the serum of women with endometriosis using SELDI-TOF-MS protein chip array technology, and this diagnostic system was shown to distinguish endometriosis from validation samples with a sensitivity of 91.7% and a specificity of 90.0%. 15 The present study was designed to search for different mitochondrial proteins in samples of eutopic endometrium from patients with adenomyosis or endometriosis, and to compare the proteins between the two diseases. The women enrolled in the study were divided into three groups: group 0 underwent laparoscopy for infertility or benign indications, and were without clinical symptoms of endometriosis during the clinical examination or visible evidence of endometriosis during surgery; group 1 had adenomyosis; and group 2 had ovarian or pelvic endometriosis.…”
Section: Mitochondrial Proteins In Adenomyosis and Endometriosismentioning
confidence: 99%